Does platelet count in platelet-rich plasma influence slope, maximal amplitude and lag phase in healthy individuals? Results of light transmission aggregometry. (3rd October 2015) - Chandrashekar, Vani
Abstract: Light transmission aggregometry lacks in standardisation and normal reference values are not widely available. The aims of our study were to establish reference ranges for aggregation, slope and lag phase in healthy controls with platelet counts between 150 and 450 × 10 9 /l in platelet-rich plasma (PRP) as well as evaluate the influence of platelet count. Ninety-nine subjects were evaluated with four agonists and divided into two groups based on platelet count and the groups were compared by Student's t -test. There was no difference between the means of the two groups for amplitude and slope barring the lag phase for collagen. Platelet counts between 150 and 450 × 10 9 /l have no effects on light transmission aggregometry and hence adjustment of platelet count is not necessary.